Personal Naming System of Bima Tribe in West Nusa Tenggara: Usage and Naming Behaviour - Sayit Abdul Karim (Register Journal, 2022)
The naming system in Bima tribe is unique and interesting to be investigated because the naming system distinguishes one individual name from others among the community. The purpose of the present study is to describe the Bimanese personal naming system in terms of its usage and naming behavior attributed to the Kempo community, one of the sub-districts within Dompu regency, Sumbawa Island, West Nusa Tenggara province. A qualitative study and descriptive analysis were employed to explain the Bimanese personal naming system, usage, and naming behavior. The naming system is related to the Semantic theory of personal names and references. The data were obtained from semi-structured interviews with some respondents in the Sub-district of Kempo. In addition, previous research findings and related documentation studies were used to support the data needed. The findings revealed that the naming system of Kempo community can be divided into four different ways, and they are varied in their usages. The naming system is unique as it distinguishes one individual name from others among the community and can be used as an instrument to manage their interpersonal relations among the community. Moreover, the Kemponese will recall their knowledge of someone's physical appearance, personal character, social relations, family background, life history records, and professions to easily recognize the person being talked.Keywords: Bimanese, community, personal naming system, usage, naming behavior